Magnetic anomaly lineations in the Northeastern South China Sea and their implications for initial seafloor spreading - Wu, Zhaocai; Zhang, Jialing; Xu, Mingju; Li, Hailong (Frontiers in Earth Science, 2023)
Ridge jumps occurred during the spreading process of the South China Sea. Recent research on the lower crustal reflectors event on seismic profiles found at least two southward ridge jumps, but only one has been confirmed by geomagnetic data. Based on magnetic anomalies in the northern South China Sea and the “two ridge jumps” model, this study identified that an early ridge jump occurred at anomaly C10n (28.3 Ma), with a southward jump of 20 km. According to the magnetic lineation distribution in the northern South China Sea, initial spreading was dominated by local punctiform break-up and the oldest anomaly, C12n (∼30.8 Ma), appeared at two turns of COB. In the IODP Expedition 367&368 drilling area, the continuity of magnetic anomalies from Ridge A to Ridge C was enhanced gradually, representing the transition from local magmatism before the final crustal break-up to a stable igneous oceanic crust. The earliest seafloor spreading magnetic lineation in the Northwestern Sub-basin is C12n (∼30.8 Ma) and the magnetic lineation corresponding to the fossil spreading ridge is C10r (∼29 Ma). The average half-spreading rate was ∼27.2 mm/yr. The opening of the Northwestern Sub-basin appears to have been rotated around a fixed point at the west, with a fault at the eastern end formed by the trajectory of the conjugate point moving during seafloor spreading.